I was wondering how you would translate an embedded conditional if the conditional in the necessary condition is negated. For example, A--->[Not (B--->C)].
My best guess would be to say that it is A--->(B Some Not C), but I don't think that is a very helpful notation. Is there a way to make this is into an "easier" to visualize conditional chain?
EDIT: Added some brackets to make the embedded condition easier to see.
Comments
I missed some parentheses. The conditional should be A--->[Not(B--->C)]. You can distribute the "not" in the necessary condition as B SOME Not C, which gets you A--->(B Some Not C). So if there is an A, then there are some Bs that aren't Cs. My question is whether or not this is the most effective translation using lawgic notation.
ADDITION: The more I think about it, the contrapositive might be easier to see. (No Bs are Not Cs)--->Not A. This would be (B--->C)--->Not A. Does this imply B--->C--->Not A? (The parentheses drop away?)
A---->B
B some /C
Negation of some is none, and negation of all is some not. So for example some A are not B would be A some /B.
I apologize if I am misunderstanding your question. There are probably some mentors or sages that could provide better guidance.
Not quite. I'm referring back to the lessons talked about here: http://7sage.com/lesson/mastery-embedded-conditional/
The necessary condition itself is a conditional statement, so A--->B SOME Not C is a different idea than A--->(B SOME Not C). Specifically, the entirety of the SOME statement is contingent on the relationship to A instead of being a discrete relationship between B and C.